Procalcitonin in Preterm Neonates: A Different Threshold and Prolonged Interpretation - Bianco, Blandine; François-Garret, Bérengère; Butin, Marine; Dalmasso, Cyril; Casagrande, Florence; Mokhtari, Mostafa; Eleni Dit Trolli, Sergio (Frontiers in Pediatrics, 2021)
Objectives: To evaluate the positive threshold of PCT for neonates of <32 weeks of gestation for the diagnosis of early-onset sepsis and to determine if the level of PCT collected within 6 h of life could be used. Design: Retrospective and bicentric study from May 2016 to April 2018. Setting: Two groups were established, neonates evaluated for PCT at birth (CordPCT) and within 6 h of life (delPCT). Patients: Two hundred and sixty neonates of <32 weeks of gestation born in Nice and South Paris (Bicêtre) University Hospitals, had been evaluated for PCT level. Main Outcomes Measures: The value of the PCT positive threshold was determined for the total population and each groups thanks ROC curves. Results: The threshold level of PCT for the total population was 0.98 ng/mL. The threshold value of cordPCT group was 1.00 vs. 0.98 ng/mL for delPCT group. The area under the Receiver Operating Characteristics curve for PCT sampled in delPCT group was significantly higher than in cordPCT group (0.94 compared to 0.75). Conclusions: The threshold level of PCT was higher in this cohort of neonates of <32 weeks of gestation compared to the value generally described for term neonates. The secondary sampling PCT level seems to be usable in screening algorithm for early-onset neonatal sepsis.